If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(v + 7) = -4v + 20 Reorder the terms: 4(7 + v) = -4v + 20 (7 * 4 + v * 4) = -4v + 20 (28 + 4v) = -4v + 20 Reorder the terms: 28 + 4v = 20 + -4v Solving 28 + 4v = 20 + -4v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '4v' to each side of the equation. 28 + 4v + 4v = 20 + -4v + 4v Combine like terms: 4v + 4v = 8v 28 + 8v = 20 + -4v + 4v Combine like terms: -4v + 4v = 0 28 + 8v = 20 + 0 28 + 8v = 20 Add '-28' to each side of the equation. 28 + -28 + 8v = 20 + -28 Combine like terms: 28 + -28 = 0 0 + 8v = 20 + -28 8v = 20 + -28 Combine like terms: 20 + -28 = -8 8v = -8 Divide each side by '8'. v = -1 Simplifying v = -1
| 3m+4=25 | | X^2+9=18 | | 3a-5=5 | | 5(4t+1)-8=t-(t+2) | | 2x-6x+1=5 | | 1.5=d+0.8 | | 5x-18=5x+38 | | x+30=4x | | 2+5x=-23 | | 6(3+4x)-2=112 | | 2(r+2)=-24 | | 5m-14-6m=-13 | | 12/5+1/7t=3 | | 1a=3a-4 | | 15r=-50 | | 18-4t=10 | | x=4x-30 | | 21=18x | | x/8-7=-1 | | 2.7a-1.5=-5.64 | | 3(2x-6)-4=3(x-2)+8 | | (6r+3e-2d)+(3r-5e+3r)-(-5r+4e-8d)= | | k/8=10/12 | | -20s-3-25s-1=0 | | 21+(6/3)x8-1+35 | | 3u+36=-7(u-4) | | 1/6b=7.4 | | (6r+3e-2d)+(3r-5e+3r)-(-5r+4e-8d)= | | 3/p=-11/10 | | 11k+6=4k+34 | | f/-17=51 | | c=8d |